Customer Satisfaction of Nokia Mobile Handset Users - Rangeswara Reddy, J. V. (Indian Journal of Marketing, 2009)
In 19th century, Prof. Alfred Graham Bell invented the telephony to talk to others. The first real improvement in the telephone was due to Thomas Alva Edison’s carbon transmitter, which was then further improved by the Blake microphone. Another improvement was the combination of mouthpiece and the earpiece into a single handset, giving a new freedom of movement to users. The individual parts of the telephone were discovered and developed by different people at different times. On February 14, 1876, the day that Graham Bell applied for a patent for his version of the telephone, Elisha Gray applied for a caveat-a document indicating that he intended to file his own patent claim within three months. But Gray was a few hours too late -Bell had already filed an actual patent application. London’s first trunk telephone line linked the city with Brighton. For the first time, telephone communication was opened between London and what were then termed ’the Midland and Northern countries’ Thomas Watson was Alexander Graham Bell’s right-hand man who helped him create the telephone. Cellular Phones are an offshoot of Graham Bell’s invention. These devices work and have to be activated with the help of an electronic chip which are provided by many service providers.The cellphone has revolutionized the way in which people communicate with each other. India has a population of 100 crores and 60% of the people use cell phones.